Infarct of the Right Basal Ganglia in a Male Spinal Cord Injury Patient: Adverse Effect of Autonomic Dysreflexia - Subramanian Vaidyanathan; Bakul M. Soni; Gurpreet Singh; Peter L. Hughes; Kamesh Pulya; Tun Oo (The Scientific World Journal)
Autonomic dysreflexia is a clinical emergency that occurs in individuals with spinal cord injury at level T-6 and above. We present a 58-year-old male patient with paraplegia who developed a severe, recurrent, throbbing headache during the night, which was relieved by emptying the urinary bladder by intermittent catheterisation. As this person continued to get episodes of severe headache for more than 6 months, computed tomography (CT) of the brain was performed. CT revealed an infarct measuring 1.2 cm in the right basal ganglia. In order to control involuntary detrusor contractions, the patient was prescribed propiverine hydrochloride 15 mg four times a day. The alpha-adrenoceptor blocking drug doxazosin was used to reduce the severity of autonomic dysreflexia. Following 4 weeks of treatment with propiverine and doxazosin, the headache subsided completely. We learned from this case that bladder spasms in individuals with spinal cord injury can lead to severe, recurrent episodes of autonomic dysreflexia that, in turn, can predispose to vascular complications in the brain. Therefore, it is important to take appropriate steps to control bladder spasms and thereby prevent recurrent episodes of autonomic dysreflexia. Intermittent catheterisations along with an alpha-adrenoceptor blocking drug (doxazosin) and an antimuscarinic drug (propiverine hydrochloride) helped this individual to control autonomic dysreflexia, triggered by bladder spasms during the night.